2013
DOI: 10.1016/j.amepre.2012.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Among Latino Children Within a Migrant Farmworker Community

Abstract: Interventions are needed that address both childhood obesity and parent weight status among Latino migrant farmworkers. Prevention programs that address the weight status of Latino children who are overweight, but not necessarily obese, are also needed, as their parents tend to be no more concerned about a child who is overweight than one who is normal weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…Early estimates from a California-based sample of preschool-aged children, most of whom lived in farmworker families, reported that 37% of children were overweight or obese [10]. Subsequent studies of youth aged 2 years and older in Latino farmworker families have reported combined overweight/obesity rates of 47% [11] 49% [12] and 76% [13]. …”
mentioning
confidence: 99%
“…Early estimates from a California-based sample of preschool-aged children, most of whom lived in farmworker families, reported that 37% of children were overweight or obese [10]. Subsequent studies of youth aged 2 years and older in Latino farmworker families have reported combined overweight/obesity rates of 47% [11] 49% [12] and 76% [13]. …”
mentioning
confidence: 99%
“…Consistent with this supposition, available evidence suggests elevated rates of overweight and obesity. 5,1214 …”
mentioning
confidence: 99%
“…Elevated rates of overweight and obesity in this population necessitate purposeful intervention, 14 but the role physical activity and sedentary living play in obesity disparities among farmworker children is unclear. Beyond weight-related prevention and treatment, descriptive information on farmworker children’s physical activity is needed to determine if targeted physical activity initiatives could meaningfully impact health disparities borne by this vulnerable group.…”
mentioning
confidence: 99%
“…1 Children of Latino farmworkers may have even greater risk. One study found 27% of children ages 3–16 in this group were obese, 2 while another found 41% of a sample of 6–11 year-old children in migrant farmworker families were overweight or obese. 3 …”
Section: Introductionmentioning
confidence: 98%